1952
DOI: 10.1113/jphysiol.1952.sp004793
|View full text |Cite
|
Sign up to set email alerts
|

The action of adrenaline and noradrenaline on the placental and foetal circulations in the rabbit and guinea‐pig

Abstract: The original object of the investigation was to find whether the placental barrier was permeable to adrenaline and to noradrenaline. It soon became apparent that whereas the placental vessels were very sensitive to these hormones, the foetus itself was relatively insensitive. These findings will now be described. METHODSThe observations were made on rabbits, 28-31 days pregnant, and guinea-pigs, 40-63 days pregnant. Light anaesthesia was maintained with urethane 1-5 g/kg body weight, injected intravenously. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Catecholamine injection in rabbits and guinea-pigs has been shown to cause foetal bradycardia, an effect which was ascribed to a severe PLACENTAL BLOOD FLOW reduction in maternal placental blood flow (Dornhorst & Young, 1952;Martin & Young, 1960). More recently, Bell (1968) has shown that noradrenaline caused constriction in isolated guinea-pig uterine arteries perfused at constant flow.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine injection in rabbits and guinea-pigs has been shown to cause foetal bradycardia, an effect which was ascribed to a severe PLACENTAL BLOOD FLOW reduction in maternal placental blood flow (Dornhorst & Young, 1952;Martin & Young, 1960). More recently, Bell (1968) has shown that noradrenaline caused constriction in isolated guinea-pig uterine arteries perfused at constant flow.…”
Section: Discussionmentioning
confidence: 99%
“…
A single intravenous injection of adrenaline or noradrenaline into the maternal circulation causes a transient bradycardia of the exposed foetus in the near-term rabbit and guinea-pig (Dornhorst & Young, 1952); this was shown to be due to asphyxia consequent upon the reduction in maternal placental blood flow caused by constriction of the uterine arteries, and not due to any accompanying activity of the uterine muscle. The purpose of the present investigation was to study the influence of gestational age on this asphyxial bradycardia, in the guinea-pig foetus in utero.
…”
mentioning
confidence: 95%
“…Moreover, although stress is capable of activating the adult ANS within seconds, the time it takes for the maternal ANS response to be measurable in the amniotic fluid is unclear. In pregnant rabbits and guinea pigs, continuous infusion of NE and EPI reduces placental blood flow causing fetal HR to decrease within 20 to 60 seconds after the infusion started (59). Likewise in humans, fetal HR decreases within 1 minute after a single injection of NE to the mother (60).…”
Section: Discussionmentioning
confidence: 99%